Effect of probiotic on the fecal slgA level in preterm infants (A randomized double-blind placebo control study) - Lucia P Retnaningtyas; Subijanto M Sudarmo; Ariyanto Harsono; Sylviati M Damanik (Paediatrica Indonesiana, 2008)
Background Secretory immunoglobulin A (slgA) plays animportant role in the defense of gastrointestinal tract. Preterminfants that developed abnormal pattern of bowel colonizationmay benefit from strategy to support maturation of humoral im-munity and endogenous production of slgA by early colonizationwith probiotic.Objective To evaluate the effect of pro biotic on the fecal slgAlevel in newborn preterm infants.Methods A randomized control study of newborn pre term infantswas conducted in NICU Dr Soetomo Hospital, Surabaya inNovember-December 2007. Pro biotic group was given multi-strain pro biotic containing 107 cfu of Lactobacillus acidophil us,Bifidobacterium longum, and Streptococcus faecium once dailyfor 14 days from second day of life. Fecal slgA was determined byELISA before and after intervention. Subjects who got respiratorydistress syndrome (RDS) or sepsis during the study was droppedout. Statistical analysis used in this study were chi-square, inde-pendent sample t-test, Mann-Whitney, Wilcoxon Signed-Rankstest, and multivariate analysis of variance (a=O.OS).Results Forty seven neonates were enrolled, seven of them weredropped out. Forty analyzed neonates were divided in probiotic(n = 20) and placebo group (n = 20). The basic characteristics oftwo groups were similar. At first examination, median of fecal slgAlevel did not differ significantly between groups (P=0.512), 0.164and 0.174mg/g feces in probiotic and placebo group respectively.There was higher increment of fecal slgA level in pro biotic thanplacebo group post treatment(1.735 versus 1.449 mg/g feces,P=0.003).Conclusion Preterm infants may benefit from probiotic becauseof the clear tendency to increase fecal slgA secretion